International student mobility in a German and Portuguese university: Which factors in the host institution matter?. (17th March 2020) - Haase, Heiko; Franco, Mario; Pedro, Eugénia
Abstract: In a globalising world, international mobility in higher education is an important phenomenon for students and higher education institutions. It is therefore essential to understand the factors that determine international students' satisfaction with higher education institutions that serve as hosts. Through research of an exploratory, quantitative nature, this study presents results from a survey among 289 incoming international students in two universities in Germany and Portugal. Our findings show that the factor we define as educational experience was an important determinant of student satisfaction. Furthermore, the appraisal of academic reputation is dependent on the university. We conclude that satisfaction with academic factors is more important for international students than satisfaction with non‐academic aspects.